2012
DOI: 10.1523/jneurosci.4799-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Projections from V1 to V2 in Amblyopia

Abstract: The mechanism of amblyopia in children with congenital cataract is not understood fully, but studies in macaques have shown that geniculate synapses are lost in striate cortex (V1). To search for other projection abnormalities in amblyopia, the pathway from V1 to V2 was examined using a triple-label technique in 3 animals raised with monocular suture. [3H]proline was injected into one eye to label the ocular dominance columns. Cholera toxin B-gold (CTB-Au) was injected in V2 to label V1 projection neurons. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This may be due, at least in part, to a reduced strength of amblyopic eye input to higher level areas (Anderson, Holliday, & Harding, 1999; Anderson & Swettenham, 2006). Thus, whereas V1 anomalies may be at the root of amblyopic impairments, they are likely to be amplified by the progressive degradation of feed-forward neural signals in the dorsal and ventral pathways (Barnes, Hess, Dumoulin, Achtman, & Pike, 2001; Choi et al, 2001; Conner, Odom, Schwartz, & Mendola, 2007; El-Shamayleh, Kiorpes, Kohn, & Movshon, 2010; Goodyear, Nicolle, Humphrey, & Menon, 2000; Ho & Giaschi, 2009; Imamura et al, 1997; Kiorpes, 2006; Kiorpes et al, 1998; Kiorpes & Movshon, 1996; Levi, 2006; X. Li, Dumoulin, Mansouri, & Hess, 2007; Muckli et al, 2006; Secen, Culham, Ho, & Giaschi, 2011; Shooner et al, 2015; Sincich, Jocson, & Horton, 2012). Indeed, several studies have shown reduced levels of activation for amblyopes than neurotypical observers as far downstream as parietal and ventral temporal cortex (Ho & Giaschi, 2009; Hyvarinen, Hyvarinen, & Linnankoski, 1981; Lerner et al, 2006; Secen et al, 2011; review by Anderson & Swettenham, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due, at least in part, to a reduced strength of amblyopic eye input to higher level areas (Anderson, Holliday, & Harding, 1999; Anderson & Swettenham, 2006). Thus, whereas V1 anomalies may be at the root of amblyopic impairments, they are likely to be amplified by the progressive degradation of feed-forward neural signals in the dorsal and ventral pathways (Barnes, Hess, Dumoulin, Achtman, & Pike, 2001; Choi et al, 2001; Conner, Odom, Schwartz, & Mendola, 2007; El-Shamayleh, Kiorpes, Kohn, & Movshon, 2010; Goodyear, Nicolle, Humphrey, & Menon, 2000; Ho & Giaschi, 2009; Imamura et al, 1997; Kiorpes, 2006; Kiorpes et al, 1998; Kiorpes & Movshon, 1996; Levi, 2006; X. Li, Dumoulin, Mansouri, & Hess, 2007; Muckli et al, 2006; Secen, Culham, Ho, & Giaschi, 2011; Shooner et al, 2015; Sincich, Jocson, & Horton, 2012). Indeed, several studies have shown reduced levels of activation for amblyopes than neurotypical observers as far downstream as parietal and ventral temporal cortex (Ho & Giaschi, 2009; Hyvarinen, Hyvarinen, & Linnankoski, 1981; Lerner et al, 2006; Secen et al, 2011; review by Anderson & Swettenham, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Amblyopia is easily modeled in animals, keeping one eye deprived of pattern vision via prolonged eyelid suture (monocular deprivation (MD)), started during the CP and protracted until adulthood [32, 33]. The procedure causes a marked ocular dominance shift towards the open eye in the binocular neurons of the primary visual cortex, determined by functional and structural empowering of the inputs emerging from the ipsilateral/spared eye, at the expense of those from the contralateral/deprived one [34].…”
Section: When Experience Affects Development: the Case Of Amblyopiamentioning
confidence: 99%
“…Some researchers have speculated that cellular interactions in amblyopia are reduced in intensity, whereas others think that sensitivity and spatial resolution are both reduced in cortical neurons stimulated by foveal projections (63) . Furthermore, it has been speculated that the cortical deficits would not necessarily occur in V1 (64) ; perhaps the problem might lie only in V2 and V3, with normal processing in V1 (65) . The following hypothesis has also been proposed in the literature: The amblyopic projections are disordered, and there is a significant reduction (or loss) of spatial resolution of cortical neurons stimulated by projections from the fovea, which is thicker in subjects with amblyopia when evaluated by optical coherence tomography (1) .…”
Section: Neural Basismentioning
confidence: 99%